2013
DOI: 10.1115/1.4025512
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Scale Demonstration of a 100-kWth Solar Thermochemical Plant for the Thermal Dissociation of ZnO

Abstract: A solar-driven thermochemical pilot plant for the high-temperature thermal dissociation of ZnO has been designed, fabricated, and experimentally demonstrated. Tests were conducted at the large-scale solar concentrating facility of PROMES-CNRS by subjecting the solar reactor to concentrated radiative fluxes of up to 4477 suns and peak solar radiative power input of 140 kWth. The solar reactor was operated at temperatures up to 1936 K, yielding a Zn molar fraction of the condensed products in the range 12–49% th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…The first consists of the direct measurement of the radiative flux using one or an array of flux sensors, which can be moved (rotated), directly providing an absolute fluxmap without the need of further processing of data or calibration (Villasmil et al, 2013). Such an approach is time consuming, and the spatial resolution is limited by the size of the sensor at the minimum and by the positioning accuracy and range of the sensor.…”
Section: Experimental Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first consists of the direct measurement of the radiative flux using one or an array of flux sensors, which can be moved (rotated), directly providing an absolute fluxmap without the need of further processing of data or calibration (Villasmil et al, 2013). Such an approach is time consuming, and the spatial resolution is limited by the size of the sensor at the minimum and by the positioning accuracy and range of the sensor.…”
Section: Experimental Characterizationmentioning
confidence: 99%
“…This field has recently picked up momentum driven by the desire for alternative, renewable and sustainable approaches for fuel processing, and material and chemical commodity production, as well as for direct, energydense, and long-term storage of solar energy. Among the existing solar-driven, non-biological chemistry routes which include solar thermochemistry, photocatalysis and photoelectrochemistry, solar thermochemistry has reached the largest scale demonstrations (up to 100 kW) (Villasmil et al, 2013;Chueh et al, 2010;Säck et al, 2016), demonstrated stability over hundreds of cycles (Malonzo et al, 2014), and enormous versatility in demonstrated chemical reactions (Scheffe and Steinfeld, 2014;Steinfeld, May 2005;Romero and Steinfeld, 2012;Bader and Lipinski, 2017).…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%
“…Scaling-up the reactor technology to 1 MW solar thermal power input has the potential of reaching a solar-tochemical energy conversion efficiency of 56% [52]. Recently, a 100 kW th reactor was tested by the Swiss Paul Scherrer Institute at the 1 MW solar furnace of CNRS-PROMES in Odeillo, France [53].…”
Section: Zn/znomentioning
confidence: 99%
“…Economically, solar-driven thermochemical water splitting and PEC water electrolysis are projected to lead to similar levelized costs of hydrogen (20)(21)(22). The power of the demonstrated thermochemical water-and CO 2 -splitting systems is usually in the range of 1-10 kW, with a few demonstration projects in the 100-kW range (23), and can remain operationally stable over many days and hundreds of cycles (15). The PEC reactors, however, are laboratory-scale demonstrations in the range of 0.1-1 W and operate stably for only hours (24,25).…”
Section: Introductionmentioning
confidence: 99%